Influence of life-history-dependent migration strategies on Atlantic salmon diets. (17th October 2019) - Bøe, Kristin; Power, Michael; Robertson, Martha J; Morris, Corey J; Dempson, J Brian; Parrish, Christopher C; Fleming, Ian A
Abstract: Migratory behaviour may vary according to the life history and demographic attributes of fish and lead to the spatial segregation of distinct population segments during the non-breeding season. In adult Atlantic salmon, spawning history differences are associated with intra-population variation in marine movements, but the degree of connectivity in spatial resource use among and within maiden and repeat spawning salmon is not well understood. We analysed muscle fatty acids (FAs), δ 13 C and δ 15 N of Atlantic salmon returning to spawn, and found significant differences among spawning histories. Maiden and alternate repeat spawning Atlantic salmon were differentiated from consecutive repeat spawners by fatty acid biomarkers associated with distinct biogeographic regions of the Labrador Sea, consistent with differential migration and divergent feeding locations. The presence and pattern of feeding contrasts among spawning history groups were further supported by dorsal muscle δ 15 N, which covaried with FA compositional values and distinguished consecutive repeat spawners from the two other groups. Because the degree of connectivity among population segments affects the ecological factors faced by such groups, an improved understanding of differential migration is necessary to better predict potential population responses to environmental change.